2010
DOI: 10.1192/bjp.bp.109.075853
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with cognitive–behavioural therapy in adolescent depression: meta-analysis

Abstract: Adding CBT to antidepressants confers limited advantage for the treatment of an episode of depression in adolescents. The variation in sampling and methodology between studies, as well as the small number of trials, limits the generalisability of the findings and any conclusions that can be drawn. Future studies should examine predictors of response to treatment as well as clinical components that may affect outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 22 publications
3
50
1
2
Order By: Relevance
“…20 There were no significant group differences on most outcome measures and limited evidence favouring pharmacotherapy or combination treatment (vs. pharmacotherapy) in achieving remission. 20 Similarly, another meta-analysis (5 trials) found that CBT conferred limited additional benefit to pharmacological treatment in depressed adolescents, 21 but the combination did reduce functional impairment in the short term, 21 which is consistent with previous work. 11 Another Cochrane meta-analysis (9 trials, N ¼ 882) assessed the effectiveness of psychological and pharmacological interventions in preventing relapse or recurrence of depression after an initial episode in children and youth up to 25 years of age, and found no difference in outcomes with either approach.…”
Section: Is Psychotherapy An Effective Treatment For Depressed Childrsupporting
confidence: 78%
“…20 There were no significant group differences on most outcome measures and limited evidence favouring pharmacotherapy or combination treatment (vs. pharmacotherapy) in achieving remission. 20 Similarly, another meta-analysis (5 trials) found that CBT conferred limited additional benefit to pharmacological treatment in depressed adolescents, 21 but the combination did reduce functional impairment in the short term, 21 which is consistent with previous work. 11 Another Cochrane meta-analysis (9 trials, N ¼ 882) assessed the effectiveness of psychological and pharmacological interventions in preventing relapse or recurrence of depression after an initial episode in children and youth up to 25 years of age, and found no difference in outcomes with either approach.…”
Section: Is Psychotherapy An Effective Treatment For Depressed Childrsupporting
confidence: 78%
“…27 A recent meta-analysis noted that, compared with CBT alone, the combination of fluoxetine and CBT may produce greater improvement in psychosocial functions but no greater reduction in residual symptoms. 28 Even for successfully treated cases, there is a high relapse rate in the next 5-10 years. Overall, approximately 50-70% of patients attending a NHS CAMHS clinic may relapse in the 10 years between mid-adolescence and young adulthood, coinciding with some of the largest educational milestones and social changes they may face over their lifetime.…”
Section: Are There Effective Treatments For Depressed Adolescents?mentioning
confidence: 99%
“…Whereas in adolescence there are a significant number of RCTs of both pharmacological and psychological interventions [7,8,9], literature in younger children (12 and under) is starkly lacking. It is possible that antidepressant medication may have a different level of efficacy in younger children and medication is also less likely to be acceptable to families of younger children.…”
Section: Introductionmentioning
confidence: 99%